The interaction of Cu(II) and Zn(II) with peptide fragment of HSPB1 and its analogs - Szebesczyk, Agnieszka; Musumeci, Domenica; Napolitano, Ettore; Kukhtenko, Halyna; Iwaniak, Paulina (Frontiers in Molecular Biosciences, 2025)
IntroductionCopper (II) and zinc (II) ions are essential microelements in the human body, interacting with numerous biologically active molecules, including proteins and peptides. The precise identification of binding sites, complete with the detailed characterization of binding amino acid residues, is of great importance. This is particularly significant in the context of uncovering the mechanisms of diseases associated with single nucleotide polymorphisms (SNPs), and consequently, developing effective treatments.MethodsTwo methodological approaches were applied to study the complexation behavior. In the first, ligand and metal ions were mixed at low pH, and complexes formed upon gradual pH increase (via NaOH addition). The formation of different complex forms at changing pH was observed, and stability constants were determined. Spectroscopic data allowed prediction of coordination modes linked to structural changes. The second approach involved complex formation in buffered solutions at fixed pH. Here, metal ion solution was added to partially deprotonated ligands, potentially influencing the complexation behavior compared to the first method.Results and DiscussionThis study highlights the importance of His-131 and Glu-126 residues in Cu2+ and Zn2+ ion binding by peptide fragments of the HSPB1 protein. These residues are essential for both the stability of the complexes and the nature of their interaction with the metal ions. Analytical methods exploring complexation behavior across a pH range of 2–10 and in buffer solutions provide a comprehensive view of the thermodynamic properties of the studied systems. This enables the prediction of their behavior under diverse conditions.